Analisis Perbandingan Fatwa-Fatwa Dalam Perspektif Mazhab Hukum Islam Dan Argumentasinya: Comparative Analysis of Fatwas Fatwas in the Perspective of Islamic Legal Schools and Their Arguments - Hasmira Rahmadani; Suci Pratama Putri; Muhammad Idham Jamal; Muhammad Rusdi (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
This study will discuss the comparison of fatwas from the perspective of four Islamic legal schools, namely Hanafi, Maliki, Syafi'i, and Hanbali. The focus of this study is on the differences in methodology and argumentation in the Istinbath legal trial. This study uses a qualitative approach using a literature review methodology from primary sources in the form of classical fiqh books and fatwa documents. The results of the study indicate that differences in the use of qiyas, istihsan and istislah methods have a significant influence on differences in fatwas. Although the results vary, all schools are based on the same Sharia foundation and emphasize Maqasid Sharia. This study shows the importance of understanding these differences as an intellectual enrichment of Islam and as a basis for tolerance towards diversity in Islamic law.